Designing N-doped carbon nanotubes and Fe–Fe3C nanostructures co-embedded in B-doped mesoporous carbon as an enduring cathode electrocatalyst for metal–air batteries. Issue 32 (28th July 2017) - Nandan, Ravi; Nanda, K. K.
Abstract : N-CNTs and Fe–Fe3 C co-embedded mesoporous boron-doped carbon (BFNCNTs) nanostructures, were designed and demonstrated as an air-cathode electrocatalyst for metal–air batteries and powering of LEDs. Abstract : Oxygen reduction and evolution reactions are of immense importance in electrochemical conversion/storage devices like regenerative/alcohol/hydrogen based fuel cells and metal–air batteries. Here, a rational facile synthesis methodology has been developed to design N-doped carbon nanotubes (N-CNTs) and Fe–Fe3 C nanostructures co-embedded in B-doped mesoporous carbon nanostructures (BFNCNTs) as a noble metal-free superior bi-functional electrocatalyst for oxygen evolution/reduction reactions. The incorporation of N and B with negligible/undetectable B–N formation and Fe–Fe3 C nanostructures leads to the superior performance by introducing plenty of defects, local heterogeneity and a high specific surface area (∼272 m 2 g −1 ). Besides, mesoporous boron-doped carbon acts as a host material for NCNTs and Fe–Fe3 C, and it offers good connectivity as well as a protective coating for durable catalysis. Remarkably, more positive onset (−30 mV) and half-wave potentials (−225 mV) with ∼94% current retention under accelerated stability test and fuel tolerance for the ORR, in combination with lower onset (422 mV) and E j =10(OER) (562 mV) potentials with high current density (190 mA cm −2 @ 0.8 V vs. Ag/AgCl) for the OER as compared to commercial state-of-the-art electrocatalysts suggest superior bifunctional behavior of BFNCNTs. The complete oxygen electrochemical activity Δ E = E j (OER)=10 − E 1/2(ORR) = 0.788 V for BFNCNTs is lower than recently reported various state-of-the-art bifunctional catalysts. Besides, a prototype battery fabrication using BFNCNTs as the cathode electrode for driving a light emitting diode has been demonstrated. Overall, BFNCNTs have potential to serve as a non-precious electrocatalyst for electrochemical energy devices.